Corrosion of carbon steel in clay compact environments at 90 °C: Effect of confined conditions. (15th May 2021) - Schlegel, M.L.; Martin, F.; Fenart, M.; Blanc, C.; Varlet, J.; Foy, E.
Highlights: Carbon steel anoxic corrosion in simulated crevice hindered by confined conditions. Heterogeneous corrosion in microcontainer due to gradual filling. Magnetite and chukanovite predominate in microcontainers. Scarcity of Fe silicate, carbonate, sulphide explained by slow solution renewal. Almost occluded condition leads to significant decrease in corrosion rate. Abstract: Corrosion of low alloy carbon steel in simulated crevices and in a perforated envelope containing a rod, mimicking the liner-overpack system, was assessed at 90 °C in anoxic water-saturated clay. Corrosion in crevices was limited (< 1 μm/year). The corroded surface exposed magnetite with a fringe of siderite. Internal corrosion of the envelope was heterogeneous due to gradual filling with porewater, and average corrosion depth for the internal rod was limited to 11.5 μm after 76 months. Magnetite was the main corrosion product replacing steel, together with chukanovite, Fe silicate, and outer siderite in areas first bathed with porewater.